Internet sex work : beyond the gaze / Teela Sanders, Jane Scoular, Rosie Campbell, Jane Pitcher, Stewart Cunningham. - Sanders, Teela; Scoular, Jane; Campbell, Rosie, 1967-; Pitcher, Jane; Cunningham, Stewart (Palgrave Macmillan, 2018)
This volume takes readers behind the screen to uncover how digital technologies have affected the UK sex industry. The authors use extensive new datasets to explore the working practices, safety and regulation of the sex industry, for female, male and trans sex workers primarily working in the UK. Insights are given as to how sex workers use the internet in their everyday working lives, appropriating social media, private online spaces and marketing strategies to manage their profiles, businesses and careers.